STUDI IDENTIFIKASI SAMPAH MIKROPLASTIK PADA SEDIMEN PASIR DI PANTAI LAMBUTOA KABUPATEN TAKALAR - Humairah, Indah Putri; Husain, Firman; Umar, Hasdinar (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Indonesia is currently one of the countries in East Asia which produces around 50% of waste coast in the world. Microplastics in Indonesian seawater range from 30 to 960 particles/liter. The purpose of this study was to determine the size, amount, type, and existing microplastic polymers on Lambutoa Beach in Takalar District. This study uses quantitative methods to examinein a particular population or sample. The research method used is a quantitative research method.Quantitative research methods study a particular population or sample, collecting data with use research tools, and analyze quantitative or statistical data for the purpose of testing and prove the hypothesis that has been formulated/set to be used. As for the steps taken during the research process, namely sand sediment sampling, sediment sample processing sand, observing and identifying types of microplastics, and testing using the FTIR tool. From the results In this study, there were 49 samples of microplastic waste with an average size of 1-5 mm. The microplastics contained in the sand sediments that have been tested have three types, namely film, fragments, and foam. For the most common type of polymer found in sediment sample testing using the FTIR tool on microplastic samples is a type of polymer Other (Nylon) and PET (Polyethylene terephthalate).